The European Union's aging population: Challenges for human resource management. (3rd September 2018) - Chand, Masud; Markova, Gergana
Abstract : The European Union (EU)'s aging population is leading to a workforce that is rapidly aging and gradually beginning to shrink. Businesses will have to prepare for an older workforce that will have different priorities compared to the historically younger workforce. In this article, we examine the aging population of the EU and analyze how organizations can best manage the transition to a workforce that is rapidly aging. We explain how the changing demographic outlook translates into challenges for acquiring and retaining talent, and how employers can best manage this transition. We provide examples of organizations that have implemented human resource policies to make their workplaces more elderly friendly and their workforces more efficient. We conclude by pointing out some steps that organizations can take to better integrate older workers and help make their aging workforces more productive.